ﺗﺄﺛﯾر إﺿﺎﻓﺔ اﻟﺑروﺗﯾن اﻟﻧﺑﺎﺗﻲ اﻟﻣﺻﻧﻊ ﻓﻲ اﻟﺻﻔﺎت اﻟﻧوﻋﯾﺔ واﻟﺣﺳﯾﺔ ﻟﻣﻧﺗوج ﻓطﺎﺋر ﻟﺣم اﻟﻌﺟل اﻟﻣﻔروم (Journal of the College of Education for Women, 2019)
The aim of this investigation was to prepare pies stuffed with ground veal as different level of Textured Soy Protein (TSP) that wetted, minced and replaced at (0, 15, 20, 25 and 30%). The effect of partial substitution for veal with TSP quality, sensory characteristics such as color and homogenizing of the stuffing, taste, flavor, juiciness and overall acceptability was evaluated by taste panel. The obtained results showed that product prepared with replaced 15 and 20% were acceptable by panel taste without significant differences compared to control. The values of taste panel score dropped as the rate partial replacement increased a level of TSP 25 and 30% as compared to control. It can be concluded the possibility of using manufactured vegetable protein such as TSP as partial replacement to veal meat that can be employed in processing pies at 20% TSP level and keeping acceptable quality and sensory properties for manufactured product.